(untitled) (Revista de Ciências Agroveterinárias, 2018)
Twenty sheep were placed in a completely randomized block design and submitted to one of five treatments testing castor cake as a ration ingredient (untreated castor cake, treated with limestone, with urea, with mono-dicalcium phosphate and autoclaved) to evaluate their performance and the economic output. The roughage consisted of tifton-85 bermudagrass hay. The market prices of the rations ingredients, body weight (BW) and the carcass weight were considered to identify the minimum conditions for the enterprise to become economically feasible. After obtaining the ration cost and the dry matter intake, the technical, zootechnical and economic indexes were analyzed using the Excel® program. The daily production (kg of BW or kg of carcass) was higher for sheep eating rations with autoclaved castor cake and treated with mono-dicalcium phosphate, showing the highest production system turnover and providing the highest number of finished animals on a yearly basis. These production systems showed the highest gross income. The animal purchase and feeding were the most representative items on BW production expenses, representing 44.8 and 43.3%/year on average, respectively. Adopting R 4.70/kg BW and R 13.40/kg carcass as sell prices, the production system containing castor cake treated with mono-dicalcium phosphate showed the best economic output, with a 1.07 benefit/cost, a R 73,117.34 liquid present value (LPV), 54% internal return rate (IRR) and a R 4.32 BW total cost. On the other hand, the production system using non-treated cake as the ingredient showed a 1.00 benefit/cost, R 1,772.62 LPV, 8% IRR and R 4.63/kg BW total cost, without any evidence of animal toxicity. It can be concluded that mono-dicalcium phosphate-treated castor cake is a promising ingredient to be used in sheep rations.